2021
DOI: 10.7759/cureus.18198
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pectoralis Major Myocutaneous Flap in Laryngectomy Surgery: Single Surgeon Experience

Abstract: Bathula et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the study conducted by Menach et al [ 19 ], the results suggest that being a former smoker confers a positive risk for laryngeal cancer across all laryngeal subsites, the highest being for supraglottic cancer (OR = 6.7), which is comparable to glottic carcinoma (OR = 6.1) when compared to the controls. Lewis, his team, and other authors demonstrated that the glottis is anatomically the narrowest part of the upper airway, and for that reason, it is more susceptible to the deposition of inhaled carcinogens found in cigarette smoke [ 20 , 21 , 22 , 23 , 24 ]. The delays in the implementation of tobacco preventive measures in countries from Eastern Europe, compared to Western Europe, are mainly responsible for the differences in mortality trends between these areas [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Menach et al [ 19 ], the results suggest that being a former smoker confers a positive risk for laryngeal cancer across all laryngeal subsites, the highest being for supraglottic cancer (OR = 6.7), which is comparable to glottic carcinoma (OR = 6.1) when compared to the controls. Lewis, his team, and other authors demonstrated that the glottis is anatomically the narrowest part of the upper airway, and for that reason, it is more susceptible to the deposition of inhaled carcinogens found in cigarette smoke [ 20 , 21 , 22 , 23 , 24 ]. The delays in the implementation of tobacco preventive measures in countries from Eastern Europe, compared to Western Europe, are mainly responsible for the differences in mortality trends between these areas [ 25 ].…”
Section: Discussionmentioning
confidence: 99%